Kepemimpinan Kepala Sekolah Dalam Pengembangan Mutu Pendidikan Perspektif Islam - Zara Karima; Arivia Shafira; Aprilia Ayu; Jilan Salma (Institut Agama Islam Negeri (IAIN) Samarinda, 2018)
Quality of education is essential to development in the world of education. A lack of attention to one of the factors of low quality education would result in such agencies being neither developed nor in learning processes nor in the technological world. Teachers are undertook and indirect teaching processes, which if the teacher's ability is inadequate and cannot develop the methods in the best possible, then the learning process will get more boring and will not advance forward because then the principal has authority in developing the quality of school education. The principal would have to be able to force new ideas, strategies and steps to develop teacher skills in the learning process, increased teacher performance and student learning interests and build good infrastructure management and ensure a periodic process of monitoring at the end of the term, late or start of the New Year's school of assessments by helping vice President, PKS and counseling coordinator.